(untitled) (Revista Direito em Debate, 2021)
The present work has as its theme the active and passive transparency as a tool for the exercise of social control in a democratic state of law in the light of participatory citizenship and the law of access to information. As a central problem the following question: Considering the prerogative of the democratic State of law, does the effectiveness of the law of Access to information have an end in itself for the exercise of social control as a way of coping with corruption? It aims to demonstrate that the importance of participatory citizenship in the conception of a democratic state of law; To identify whether the access to Information Act is a direct way of exercising social control; and analyze the challenges and effectiveness of the access to Information Act after its entry into force in relation to compliance with the requirements of the parameters of transparency and coping with corruption. For this, we used as a parameter the data from the last report made available by the Court of Auditors of Rio Grande do Sul in relation to the municipalities of the state. The methodology used was the bibliography, and also used the visitation process on the website of the Court of Auditors of Rio Grande do Sul. Thus, it is concluded that active and passive transparency are tools of means to effectise social control and, in effect, to inhibit the practice of corruption in public management.